ANALISIS SPASIAL TEMPORAL PERUBAHAN TUTUPAN LAHAN AKIBAT PEMBEBASAN LAHAN PEMBANGUNAN BANDARA INTERNASIONAL KERTAJATI - Purwaningsih, Yuli; Wibowo, Adi; Setiawan, Heri (J SIG (Jurnal Sains Informasi Geografi), 2024)
The development of the Kertajati International Airport project in Majalengka Regency, West Java, directly impacts land cover change. The land cover change comes from land acquisition by residents in Kertajati, Bantarjati, Kertasari, Sukamulya, and Sukakerta Villages. This study aims to analyze land cover changes before and after the construction of Kertajati International Airport in each village and analyze the process of residential land acquisition and the airport construction process spatially and temporally. This research uses a spatial-temporal analysis method by comparing land cover before and after the construction of Kertajati International Airport in each village and visual interpretation using Google Earth image data in 2009, 2013, 2015, 2016, 2017, 2018, 2019, 2020, 2021, 2022, and 2023. The results showed that land cover change affected paddy fields, settlements, and moorlands. The most affected paddy fields are in Kertajati and Bantarjati Villages. Then, the most affected residential land is Kertasari Village. Land clearing of residential land was carried out in different years for each village due to the land acquisition process. The construction of Kertajati International Airport was carried out from 2013 to 2018, but after this period, there was still an additional runway in Sukamulya Village. This research proves that Google Earth imagery can help analyze land cover change.